2017
DOI: 10.1039/c7cc04222a
|View full text |Cite
|
Sign up to set email alerts
|

Isoreticular expansion of polyMOFs achieves high surface area materials

Abstract: Polymer–MOF hybrid materials (polyMOFs) are shown to adhere to the principle of isoreticular expansion, generating polyMOFs with large surface areas and enhanced stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 36 publications
1
40
0
Order By: Relevance
“…In contrast with other polymer‐MOF hybrid systems, polyMOFs use pre‐synthesized organic polymers containing H 2 bdc units that act as ligands for MOF preparation. In a series of reports, a variety of polyMOF structures, including IRMOFs, UiO‐66, pillared‐MOFs, and isoreticular structures with laterally extended linkers have been described ,. All polyMOFs to date are synthesized from ligands connected through para ‐substituted terephthalic acid (H 2 bdc) with alkoxy linkages of various lengths (Figure ).…”
Section: Figurementioning
confidence: 99%
“…In contrast with other polymer‐MOF hybrid systems, polyMOFs use pre‐synthesized organic polymers containing H 2 bdc units that act as ligands for MOF preparation. In a series of reports, a variety of polyMOF structures, including IRMOFs, UiO‐66, pillared‐MOFs, and isoreticular structures with laterally extended linkers have been described ,. All polyMOFs to date are synthesized from ligands connected through para ‐substituted terephthalic acid (H 2 bdc) with alkoxy linkages of various lengths (Figure ).…”
Section: Figurementioning
confidence: 99%
“…[40b] In addition, polyMOFs conform to the principle of isoreticular chemistry,allowing for linear extension of the organic linker groupts to obtain polyMOFs with even greater surface areas (> 1500 m 2 g À1 ). [41] Recently MacLeod and Johnson reported on as eries of block co-polyMOFs,where uniform benzene-1,4-dicarboxylic acid dimers or tetramers were attached as endgroups to ap olystyrene polymer. [42] These block copolymers were treated with Zn 2+ under solvothermal conditions.Copolymers containing benzene-1,4-dicarboxylic acid dimers did not form polyMOFs,suggesting alower limit on block size required to obtain crystalline phases.H owever,t he tetramer-terminated copolymers formed ab lock co-polyMOF (BCPMOF) that displayed distinct phase separation between the "hard" polyMOF block and the "soft" polystyrene block (when imaged by TEM).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Cohen and co-workers demonstrated that certain linear organic polymers with aromatic dicarboxylic acids in their backbones could be used as ligands to synthesize highly crystalline and porous MOFs, called polyMOFs. [129,[168][169][170] A series of polymer ligands were synthesized ( to prepare polyMOFs with crystalline structures isostructural to MOF-5, [Zn 2 (bdc) 2 (dabco)], [Zn 2 (bdc) 2 (4,4′-bpy)], UiO-66, UiO-67, and UiO-68, respectively. The polyMOFs showed a permanent porosity, as their parent MOF structures do, and some of these polyMOFs inherited the hydrophobicity of their polymer ligands.…”
Section: Maf-x12mentioning
confidence: 99%